Urbanization reshapes a food web. Issue 3 (17th December 2019) - Start, Denon; Barbour, Matthew A.; Bonner, Colin
Abstract: Cities represent humanity's most intense impact on our planet, with more than half of all humans now residing in urban areas. Indeed, urbanization has well‐understood impacts on both individual species and general patterns of biodiversity. However, species do not exist in isolation, but are instead members of complex interaction networks that shape patterns of diversity and influence ecosystem services. Despite the importance of species interaction for creating patterns of diversity, we do not understand how urbanization alters these interactions. Here, we investigate how an interaction network (food web) is reshaped by urbanization. We show that, consistent with theory, cities tend to support less diverse ecological communities, and rare species that interact with few species are particularly sensitive to urbanization. As a result, remnant urban food webs tend to have more interactions per species and greater connectance, creating more integrated interaction networks. We discuss the implications of this food web reshaping for ecological stability, eco‐evolutionary dynamics, and the joining of interaction networks and conservation planning. The role of cities in reshaping interaction networks provides an interesting study of food web (dis)assembly, while also shedding light on new approaches to applied conservation issues. Abstract : Cities represent humankind's most intense impact on our planet. While we increasingly understand how urbanization shapes individual species and communities, we know relatively little about if and how cities rewire interaction networks—key providers of ecosystem services. We show that urban environments qualitatively alter the structure and function of a food web, with possible consequences for evolutionary change, conservation and ecosystem services.